Development of professional integration of digital competences in the Czech Republic legal sector: A Qualitative Research - Jan MAGINEC; Jaroslav VETESKA (Communications of International Proceedings, 2025)
This study examines the development of digital competences among legal professionals, specifically attorneys and judges, in the Czech Republic. Drawing on a qualitative methodology, semi-structured interviews with 32 respondents are used to analyse how selected legal professionals perceive and develop digital competences, with the results indicating that attorneys are more active in the field of digitalization, particularly due to the direct impact of technologies on their practice and competitiveness, while judges, by contrast, display a more reserved approach, influenced in part by the structure of the judicial system. The research points to the need for systematic professional education in digital technologies and the importance of strategic support for developing digital competences in the legal environment. These findings correspond with international trends that emphasize the necessity of reflective and practice-oriented education. The development of digital competences should be understood not only as a technical innovation but also as part of the professional identity of attorneys and judges in the era of Industry 5.0.
Keywords: digital competences; legal professionals; lifelong learning; professional education